Advanced portfolio management using markowitz portfolio theory - Kundu, Souvik; Khan, Mustaqim; Rahman, Faisal (Brac University, 2020)
This thesis is submitted in partial fulfillment of the requirements for the degree of Bachelor of Science in Computer Science, 2019.